Geoeconomic and Technological Implications of Critical, Strategic, and Rare Earth Minerals for Sustainable Power Generation - Shutika R. Kamble; Gunwant G. Wadpalliwar; Sadhana S. Kambale (IJRDO Journal of History & Geography, 2026)
The transition to low-carbon electricity systems is increasing demand for critical, strategic, and rare-earth element minerals used in power generation, storage, hydrogen technologies, and electricity networks. This research accounts for the importance of these minerals for future power-system development by connecting to scenario-based mineral demand with concentration in the supply chain. Demand was calculated for solar PV, wind power, grid battery storage, electricity networks and hydrogen for Stated Policies Scenario (STEPS), Announced Pledges Scenario (APS) and Net Zero Emissions by 2050 Scenario (NZE scenarios), using the International Energy Agency Critical Minerals Dataset. The assessment of supply exposure was conducted by examining the top three supplier concentration at the mining and refining, lithium chemicals and battery-grade graphite stages. The results indicate that the most significant mineral demand under NZE is for electricity networks, totaling 8,853 kt in 2050, and copper is the most significant mineral demand at its lowest level, at 13,936.3 kt in 2050. Grid battery storage, solar PV, and wind form the next major demand cluster. REEs, especially neodymium, praseodymium, dysprosium, and terbium, remain strategically significant despite lower mass demand because of their role in permanent-magnet wind technologies and concentrated supply chains. The study concludes that mineral security must be integrated into power-sector planning through supply diversification, responsible sourcing, recycling, and material efficiency.